(untitled) (diségno, 2019)
The history of architecture has been punctuated by transformations sparked by sudden technological leaps. During the mid-1400s, into the context of a craft-based architectural tradition, Leon Battista Alberti introduced a mathematical approach to graphic representation. In doing so, he paved the way for Renaissance classicism: architecture focused on precision and representation through drafting rather than approximate construction by artisans. Four centuries later, steel and glass enabled engineers like Isambard Kingdom Brunel, Sir Joseph Paxton, and Gustav Eiffel to design daring and innovative structures that shattered the limits of what could be constructed. Soaring feats of technological prowess became a new aesthetic at the nexus of architecture and engineering. A generation later, at the crest of the mechanical era, Le Corbusier appropriated the tools and forms of mass production, and concluded that the house is a machine for living in. Architecture was optimized not only from the standpoints of design and structural engineering but also from those of mass production and social function. (read more)